2023
DOI: 10.3390/ijms24032267
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Molecular Interactions of Nano- and Microparticles in Dental Implantology

Abstract: The role of metallic nano- and microparticles in the development of inflammation has not yet been investigated. Soft tissue biopsy specimens of the bone bed taken during surgical revisions, as well as supernatants obtained from the surface of the orthopedic structures and dental implants (control), were examined. Investigations were performed using X-ray microtomography, X-ray fluorescence analysis, and scanning electron microscopy. Histological studies of the bone bed tissues were performed. Nanoscale and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…182 Other recent research with soft tissue biopsies from orthopedic and dental implants concluded that nanoscale metallic particles play a role both in physiological and pathophysiological reactions of the immune system and may participate in osseointegration and disintegration of dental implants. 183 When the amount of particles crosses a threshold called "Critical Dose of Nanoscale Metallic Particles," a local intensification of inflammation is observed, with early death of immune cells and failed removal of debris, leading to further accumulation of nanoparticles and chronic inflammation. The authors claimed that mucositis and peri-implantitis could be related to the accumulation of metal nanoparticles in the bone bed as a precipitant factor for aseptic inflammation with an autoimmune component.…”
Section: Findings From In Vivo Oral Biopsiesmentioning
confidence: 99%
See 3 more Smart Citations
“…182 Other recent research with soft tissue biopsies from orthopedic and dental implants concluded that nanoscale metallic particles play a role both in physiological and pathophysiological reactions of the immune system and may participate in osseointegration and disintegration of dental implants. 183 When the amount of particles crosses a threshold called "Critical Dose of Nanoscale Metallic Particles," a local intensification of inflammation is observed, with early death of immune cells and failed removal of debris, leading to further accumulation of nanoparticles and chronic inflammation. The authors claimed that mucositis and peri-implantitis could be related to the accumulation of metal nanoparticles in the bone bed as a precipitant factor for aseptic inflammation with an autoimmune component.…”
Section: Findings From In Vivo Oral Biopsiesmentioning
confidence: 99%
“…The authors also recommended delayed dental implantation to achieve successful long-term osseointegration instead of immediate loading so that the immune system could to eliminate the metallic particles accumulated during the insertion before loading and before microbial contamination. 183…”
Section: Findings From In Vivo Oral Biopsiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[4]. One of the reasons for the development of such complications is probably the release of nanoparticles of the oxide layer of the dental implant in the tissue of the bone bed [2,7]. The accumulation and conglomeration of such particles, as well as their biocorrosion, can probably be a personalized cause of the development of mucositis and peri-implantitis, which is associated with the inability of the cells of the immune system to timely utilize these particles, preventing their conglomeration, and their early death.…”
Section: Introductionmentioning
confidence: 99%